IMPLEMENTASI HUKUM CAGAR BUDAYA PERSPEKTIF HUKUM ADAT DAYAK KALIMANTAN TENGAH - Ria Ancoi; Natalia Susilawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The problem of cultural heritage protection in Indonesia is characterized by a gap between the existence of comprehensive legal regulations and their implementation in practice. Although Law Number 11 of 2010 on Cultural Heritage provides a strong legal framework for the protection, development, and utilization of cultural heritage, various challenges such as limited institutional capacity, low public participation, and pressures from development and modernization continue to threaten the sustainability of cultural heritage. This study aims to analyze the implementation of cultural heritage law and examine the contribution of Dayak customary law in strengthening sustainable cultural heritage protection in Central Kalimantan. This research employs a normative legal method using statutory and conceptual approaches. Data were collected through a literature review of primary and secondary legal materials and analyzed qualitatively. The findings reveal that the implementation of cultural heritage law still faces obstacles in designation, supervision, institutional capacity, and community participation. Meanwhile, Dayak customary law plays a significant role through local wisdom, customary norms, singer sanctions, and customary institutions that promote collective awareness and cultural preservation. The study highlights the importance of integrating national law and customary law to achieve more effective, participatory, and sustainable cultural heritage protection. ABSTRAK Permasalahan perlindungan warisan budaya di Indonesia masih ditandai oleh kesenjangan antara kuatnya regulasi hukum dan lemahnya implementasi di lapangan. Meskipun Undang-Undang Nomor 11 Tahun 2010 tentang Cagar Budaya telah mengatur perlindungan budaya secara komprehensif, berbagai kendala seperti keterbatasan kelembagaan, rendahnya partisipasi masyarakat, serta tekanan pembangunan dan modernisasi masih mengancam keberlanjutan warisan budaya. Penelitian ini bertujuan menganalisis implementasi hukum cagar budaya serta mengkaji kontribusi hukum adat Dayak dalam memperkuat perlindungan warisan budaya berkelanjutan di Kalimantan Tengah. Penelitian menggunakan metode hukum normatif dengan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Data diperoleh melalui studi kepustakaan terhadap bahan hukum primer dan sekunder yang dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa implementasi hukum cagar budaya masih menghadapi berbagai hambatan pada aspek penetapan, pengawasan, kelembagaan, dan partisipasi masyarakat. Di sisi lain, hukum adat Dayak berperan efektif melalui nilai kearifan lokal, norma adat, sanksi singer, serta kelembagaan adat yang mampu menjaga keberlanjutan budaya berbasis kesadaran kolektif. Penelitian ini menegaskan pentingnya integrasi hukum nasional dan hukum adat untuk mewujudkan perlindungan warisan budaya yang lebih efektif, partisipatif, dan berkelanjutan.